Effect of Tempe Flour Supplementation During Pregnancy on Blood Sugar and Lipid Profile Study on Wistar Rats which Gets Restricted Diet during Pregnancy - Wibowo, Joko Wahyu (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Low birth weight (<2500 grams) is representation of a nutritional deficiency during pregnancy, this condition is associated with increased incidence of degenerative diseases. Tempe as traditional Indonesian food has the potential to improve of DNA damage and to inhibit the progression of degenerative diseases. This study aimed to determine the effect of tempe flour supplementation during pregnancy on blood sugar and blood lipid profiles of offsringMethods: An experimental study with a sample of 20 female Wistar rats were pregnant, were divided into 4 groups. Treatment during pregnancy: the first group received a diet 50% of the normal diet (10 g / day), group II get a normal diet and 50% tempe flour 1 g / day, group III received normal diet and 50% tempe flour 2 g / day, group IV, 50% received a normal diet and 1 g egg chicken / day. Provision of drinking with distilled water ad libitum. During lactation are given a normal diet, after weaning are given a diet high in saturated fat for 4 weeks in each group.Results: The mean number of children in group 1: 9.33 with a mean BB: 4.93 g, group II: with a mean of 6.17 BB: 5.32, group III: 5.17 with a mean BB: 5.33, group IV : BB with a mean of 6.33: 5.01. There are significant differences in the levels of blood sugar, total cholesterol, triglycerides, LDL, and HDL in each treatment group (p= 0,00). Conclusion: Supplementation of tempe flour effect on blood sugar levels and lipid profiles rat pups that received a restricted diet during pregnancy (Sains Medika, 4(2):182-194).